Wall-thickness-dependent strength of nanotubular ZnO - Kang, Na-Ri; Kim, Young-Cheon; Jeon, Hansol; Kim, Seong Keun; Jang, Jae-il; Han, Heung Nam; Kim, Ju-Young (NATURE PUBLISHING GROUP, 2017)
We fabricate nanotubular ZnO with wall thickness of 45, 92, 123 nm using nanoporous gold (np-Au) with ligament diameter at necks of 1.43 mu m as sacrificial template. Through micro-tensile and micro-compressive testing of nanotubular ZnO structures, we find that the exponent m in (sigma) over bar proportional to (rho) over bar (m), where (sigma) over bar is the relative strength and (rho) over bar is the relative density, for tension is 1.09 and for compression is 0.63. Both exponents are lower than the value of 1.5 in the Gibson-Ashby model that describes the relation between relative strength and relative density where the strength of constituent material is independent of external size, which indicates that strength of constituent ZnO increases as wall thickness decreases. We find, based on hole-nanoindentation and glazing incidence X-ray diffraction, that this wall-thickness-dependent strength of nanotubular ZnO is not caused by strengthening of constituent ZnO by size reduction at the nanoscale. Finite element analysis suggests that the wall-thickness-dependent strength of nanotubular ZnO originates from nanotubular structures formed on ligaments of np-Au.
Keywords: NANOPOROUS GOLD; ELASTIC PROPERTIES; ULTRA-STRONG; NANOSTRUCTURES; EVOLUTION; BEHAVIOR; TENSILE; ENERGY; FILMS